The mystery of numbers - Schimmel, Annemarie, 1922-2003 (Oxford University Press, 1993)
"Why is the number seven lucky - even holy - in almost every culture? Why do cats have nine lives (except in Iran, where they have seven)? From literature to folklore to private superstitions, numbers play a conspicuous role in our daily lives. But in this fascinating book, Annemarie Schimmel shows that numbers have been filled with mystery and meaning since the earliest times, and across every society."